Factors Associated with Knee Stiffness following Surgical Management of Multiligament Knee Injuries - Hanley, Jessica; Westermann, Robert; Cook, Shane; Glass, Natalie; Amendola, Ned; Wolf, Brian R.; Bollier, Matthew (The Journal of Knee Surgery, 2017)
Postoperative knee stiffness can influence outcomes following operative treatment of multiligament knee injuries (MLKIs). The purpose of this study was to evaluate patient and surgical factors that may potentially contribute to stiffness following surgery for MLKIs. All surgically managed MLKIs involving two or more ligaments over a 10-year period at a single level one trauma center were included in this study. A retrospective review was performed to gather objective data related to the development of knee stiffness after surgery. Patients were classified as “stiff” postoperatively if they (1) had a flexion contracture greater than 10 degrees, (2) failed to reach 120 degrees of flexion at final follow-up, or (3) underwent a manipulation under anesthesia with or without arthroscopic lysis of adhesions to improve range of motion. Patient and surgical factors were evaluated systematically to determine factors associated with stiffness. The mean age of the cohort was 27.6 years at the time of surgery and mean follow-up was 50 weeks. Overall, 26/121 (21.5%) knees were diagnosed with postoperative stiffness. In the acute postoperative phase, 17 patients underwent manipulation under anesthesia. There were no significant differences in age, body mass index, associated injuries, mechanism, external fixation use or surgical timing (acute vs. chronic) between stiff and normal knees. Factors associated with the development of postoperative stiffness included knee dislocation (p = 0.04) and surgical intervention on three or more ligaments (p = 0.04). Careful attention to postoperative rehabilitation regimens should be given to patients with knee dislocations and/or those undergoing reconstruction or repair of three or more injured ligaments. Surgeons may utilize spanning external fixation if necessary without increasing the rate of long-term stiffness. Further, acute surgery does not appear to influence rates of postoperative stiffness or the need for manipulation.
Keywords: multiligamentous knee injury; knee dislocation; knee stiffness